The relationship between technology infrastructure and bank credit: How should management promote ASEAN economies? - Bui, Ngoc Toan; Doan, Thu Trang Thi (Zielona Góra: Faculty of Economics and Management Press)
Purpose: This study aims to analyze the causal relationship between technology infrastructure and bank credit, as well as the impact of this relationship on economic growth in ASEAN economies. Design/methodology/approach: To achieve this objective, the authors model the simultaneous relationship between these factors using a panel vector autoregressive (PVAR) approach. Findings: The estimation results indicate a positive correlation between technology infrastructure and bank credit.
Keywords: ASEAN; bank credit; technologies infrastructure